2018
DOI: 10.1111/jfpe.12833
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic‐assisted extraction of betalains from red beet (Beta vulgaris L.)

Abstract: In this work, ultrasonic‐assisted extraction was evaluated for obtaining red beet extracts rich in betalains. Experiments evaluated the effects of operating variables (temperature, time, and ratio of ethanol to water) using a Box–Behnken experimental design, allowing the determination of conditions that maximize the removal of betacyanins and betaxanthins. The results indicate that the extracts obtained had higher betacyanins’ levels (0.11–4.24 mg/g) than betaxanthins (0.02–2.89 mg/g) for all experimental cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
36
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 31 publications
7
36
0
1
Order By: Relevance
“…Most likely, this can be explained by the fact that the values of total phenolic contents (TPC) and the betalains were similar in the studied samples (p>0.05). According to Silva et al (2018), in red beet extracts, there is a positive correlation between TPC and antioxidant activity via the DPPH method, and between betalains content and antioxidant activity via the FRAP method.…”
Section: Resultsmentioning
confidence: 99%
“…Most likely, this can be explained by the fact that the values of total phenolic contents (TPC) and the betalains were similar in the studied samples (p>0.05). According to Silva et al (2018), in red beet extracts, there is a positive correlation between TPC and antioxidant activity via the DPPH method, and between betalains content and antioxidant activity via the FRAP method.…”
Section: Resultsmentioning
confidence: 99%
“…favored the removal of betalains, however, at 60°C the extraction yield was reduced. Silva et al (2018) reported that the increase in temperature from 30°C to 60°C in the UAE resulted in reduction of ~17% in the betaxanthins content from red beets.…”
Section: Effect Of Time and Temperature On The Extraction Of Betalainsmentioning
confidence: 99%
“…Although the literature presents studies related to obtaining betalains from UAE (Laqui-Vilca, Aguilar-Tuesta, Mamani-Navarro, Montaño-Bustamente, & Condezo-Hoyos, 2018;, especially red beet (Silva, Silva, & Bolanho, 2018), the correlation of experimental data with the diffusion coefficient of betacyanins and betaxanthins in water has not yet been explored, which has aroused interest in conducting the present study.…”
Section: Introductionmentioning
confidence: 99%
“…In Equation (1), values of ε = 6.5 × 10 4 M −1 cm −1 and MW = 550 g/mol were used for betacyanin. For betaxanthins, reported values of ε = 4.8 × 10 4 M −1 cm −1 and MW = 308 g/mol were utilized [41,42].…”
Section: Determination Of Betalains Contentmentioning
confidence: 99%